Pendampingan Kader dalam Skrining Risiko Kehamilan Berbasis Skor Poedji Rochjati di Desa Daala Timur Kecamatan Bulo - Nur Anita; Sitti Aras Diana; Hardiman Hardiman; Nur Aisyah; Husnul Hatima (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Maternal mortality remains a major public health issue, particularly due to pregnancy complications that can be prevented through early detection and appropriate referral. Community health cadres have a strategic role in supporting maternal health services at the community level, especially in identifying high-risk pregnancies. However, cadres’ knowledge and skills in using pregnancy risk screening tools are often limited. This community service activity aimed to improve cadres’ knowledge and ability in conducting pregnancy risk screening using the Poedji Rochjati Score Card in Daala Timur Village, Bulo Subdistrict. The activity was conducted through education, demonstration, direct practice, mentoring, discussion, and evaluation using pre-test and post-test. The participants consisted of 10 health cadres, and pregnancy risk screening was conducted on 16 pregnant women. The results showed that before the education and mentoring, all cadres, 10 people or 100%, had poor knowledge and had never used the Poedji Rochjati screening tool. After the activity, 8 cadres or 80% had sufficient knowledge, while 2 cadres or 20% still had poor knowledge. The screening results among pregnant women showed that 6 women or 37.5% were classified as low-risk pregnancies, 4 women or 25% as high-risk pregnancies, and 6 women or 37.5% as very high-risk pregnancies. In total, 62.5% of pregnant women were categorized as high-risk and very high-risk. This activity had a positive impact on increasing cadres’ knowledge and strengthening early detection of pregnancy risks at the community level. Continuous mentoring, periodic evaluation, and collaboration among cadres, village midwives, health centers, and village government are needed to optimize maternal and neonatal safety.